KONTRUKSI SOSIAL ATAS FENOMENA “GUS GUS AN”: RELIGIUSITAS, GAYA HIDUP MEWAH, DAN KONTROVERSI MORAL DI MATA PUBLIK - Muhammad Daffa Rizki Abidin; Ahmad Ridwan M. Sosio; Fransiscus Xaverius Sri Sadewo M. Si (Jurnal Ilmiah Sosiologi Agama (JISA), 2026)
The phenomenon of “gus-gus-an” reflects a significant shift in how the public interprets the identity of gus as young religious figures in the digital era. These gus no longer appear solely as successors of pesantren traditions but also as public figures who construct their image through social media, creating a paradox between their sermons on modesty and their luxurious lifestyles or controversial behaviors. This study aims to analyze how society constructs meaning around this phenomenon using Peter L. Berger's theory of social construction. The research employs a qualitative approach with digital observation, document analysis, and interviews with ten informants from diverse social backgrounds. The data were analyzed thematically and integrated with the concepts of externalization, objectivation, and internalization. The findings indicate that digital media serve as the primary arena for gus to externalize their identities. The public then engages in objectivation through moral judgments, comments, and the formation of labels such as “hedon gus” or “celebrity gus.” This process continues into internalization as society develops new expectations of religious figures based on the consistency between their words and actions. The study concludes that the identity of contemporary gus is a socially negotiated construction shaped by personal expression, mediatization, and public moral perception. This phenomenon illustrates a shifting landscape of religious authority within digital culture.